The effects of government bonds on liquidity risk and bank profitability in Cape Verde - José Carlos Teixeira; Carlos Vieira; Paulo Ferreira (International Journal of Financial Studies, 2021)
To analyze the effects of government debt securities on the liquidity risk and profitability of banks in Cape Verde, this research employs an unbalanced panel dataset from 2000 to 2017 on the activity of all commercial banks operating at the end of 2017 (seven in total). The study employs models with lagged regressors, estimated by the ordinary least squares estimation method. The results show that government debt securities have no effect on bank liquidity risks, but they have an effect on bank profitability, with government debt securities having a positive impact on assets' profitability, in the long run. When government debt securities include Consolidated Securities of Financial Mobilization, the effects on profitability are negative both in the short and the long run. The study concludes that banks' strategy to hold the more conventional government debt securities as safe assets and risk-free alternative for the domestic application of liquidity surpluses is appropriate and a viable way to gain profitability in the long run. These results show the negative effect of government debt securities when the Consolidated Securities of Financial Mobilization are included, which helps to explain the low average profitability rates of Cape Verde's banks, when compared to other similar sub-Saharan African countries, like Mauritius or Seychelles.
Keywords: E43; G21; H63; 330; bank liquidity risk; bank profitability; Cape Verde; panel data; public debt securities